PENERAPAN GREEN CONSTRUCTION PADA PROYEK PEMBANGUNAN TOD MAHATA MARGONDA - Muthia Utari Masloman; Afrizal Nursin (Politeknik Negeri Jakarta, 2021)
Environmental damage and global warming has become an issue in the world. Developments in the construction project has a large influence in environmental change on the surface of the earth. Construction activities start from the constructing stage to the operating stage. Green construction is one part of the sustainable development that is required to participate in environmental sustainability. With this background, the author agreed to explain the criteria, stages of difficulty and obstacles in implementing Green Construction. Data collected by questionnaire method and data analysis using SPSS Statistics 26. The results of this study obtained the value of the Green Construction criteria that applied is waste project variables with an average value of 3,748 and the lowest is site project variables with average 3,198. The most dominant factor of difficulty in applying Green Construction is the water usage variable with an average value of 3,283 and the lowest difficulty in applying is the energy variable with an average of 2,817. The most challenging obstacle factor in implementing Green Construction is the cost factor with an average value of 4.00 and the lowest obstacle is the efficient design variable with an average of 2.96. Thus, from the results of this study is expected that the contractor can help more actively in improving the implementation of Green Construction in this construction project. Keywords: Green Construction, Obstacles, Level of Difficulty, Level of Application, Construction Project.